Potential Third-party Radiation Exposure from Patients Undergoing Therapy with 131I for Thyroid Cancer or Metastases. Issue 3 (March 2015) - D'Alessio, Daniela; Giliberti, Claudia; Benassi, Marcello; Strigari, Lidia
Abstract : Abstract: The purpose of this work is to evaluate the potential third-party radiation exposure from patients undergoing therapy with 131 I for ablation of residual thyroid tumor or metastases, based in part on serial measurements of exposure rates. Exposure rate measurements were performed at 1 m and 5 cm from the surface of each treated patient until patient release. Dose estimates based on measured exposure rates were compared with those based on analytic point-source (PSM) and line-source (LSM) models. Effective doses D(∞) to travelers, co-workers and sleeping partners were estimated by using the standard gamma factor (Γ) and the physical half-life or the values derived from measured data. Seven hundred ten patients were studied until the exposure at 1 m was below the constraints of 0.010 mSv. The 131 I activities administered ranged from 1.85 to 11.0 GBq (median: 3.7 GBq), according to the therapeutic requirements. Based on the PSM and an experimental Γ, the mean/maximum estimated D(∞) to sleeping partners, partners, travelers, and co-workers were 2.60/20.65, 0.32/2.53, 0.96/7.59, and 0.57/4.50 mSv, respectively. Using the LSM and an experimental Γ, the D(∞) values were 2.41/19.15, 0.32/2.50, 0.83/6.62, and 0.57/4.42 mSv, respectively, while they were almost double using the theoretical Γ. The results presented, based on measured data in a large cohort of 131 I-treated thyroid cancer patients, will allow more accurate estimation of potential third-party D(∞) following patient release and thus may be used to better inform physicians and hospital staff on recommendations for patient release and post-release precautions following radioiodine therapies.